Nonlinear magnetoelectric effect in a ring composite heterostructure - V. I. Musatov; F. A. Fedulov; D. V. Savelev; E. V. Bolotina; L. Y. Fetisov (Российский технологический журнал)
Objectives. The relevance of the study of magnetoelectric (ME) effect in ring ferromagnetic–piezoelectric heterostructures is due to the possibility of creating various ME devices having improved characteristics. A detailed investigation of the nonlinear ME effect in a ring composite heterostructure based on lead zirconate titanate (PZT) piezoceramics and Metglas® amorphous ferromagnetic (FM) alloy under circular magnetization is presented.Methods. The ME effect was measured by the low-frequency magnetic field modulation method. Excitation alternating- and constant magnetic bias fields were created using toroidal coils wound on a ring heterostructure for circular magnetization of the FM layer.Results. When excited with circular magnetic fields in a non-resonant mode, the ME ring heterostructure generates a nonlinear ME voltage of higher harmonics. The field and amplitude dependencies of the first three ME voltage harmonics were investigated. ME coefficients were obtained for the linear ME effect α(1) = 5.2 mV/(Oe·cm), the nonlinear ME effect α(2) = 6 mV/(Oe2·cm), and α(3) = 0.15 mV/(Oe3·cm) at an excitation magnetic field frequency f = 1 kHz. The maximum amplitudes of the 1st and 3rd harmonics were observed at a constant bias magnetic field H ~ 7 Oe, which is almost two times smaller than in planar PZT–Metglas® heterostructures.Conclusions. A nonlinear ME effect was observed and investigated in a ring heterostructure based on PZT piezoceramics and Metglas® amorphous FM alloy. Due to the absence of demagnetization during circular magnetization of the closed FM layer, nonlinear ME effects are detected at significantly lower amplitudes of the exciting alternating and constant bias magnetic fields as compared to planar heterostructures. The investigated ring heterostructures are of potential use in the creation of frequency multipliers.